Characterization and Application of Levan Produced by Halophilic bacterium Salinivibrio budaii TG2 indigenous from Gresik Salt Work of East Java as the Nanoparticle System for Lipase Immobilization - Fithriah - Nim: 10513032 , Aidah
Levan is a fructo-oligosacharide produced by certain microorganisms or plants that have enzymes to catalyze its biosynthesis i.e. levansucrase. Levan has been widely applied in various industries ranging from food to healthcare industries. Currently, levan has also been applied in the field of nanotechnology because some studies have shown that levan can be used to make nanoparticles system as a carrier for catalysts, metal ions, and drugs. In this study, several halophilic bacteria indigenous from Gresik salt work East Java have been screened their potential as a levan producer. The screening results found Salivibrio budaii TG2 as the most potential levan producer. Optimization of levan production is carried out in this work by studying levansucrase secreted by this bacterium. Optimization results showed that levansucrase works optimally when the bacteria were grown in a production medium containing 15%(w/v) NaCl and 5%(w/v) sucrose in condition pH 5 for 18 hours at 37 oC in a rotary incubator. Levan production is characterized its structure with Fourier transformed infrared (FTIR) spectrophotometer and compared the resulted spectrum to that of the standard one. After that, levan was then used to make a nanoparticle system to immobilize lipase. The resulted nanoparticles were analysed with scanning electron microscope (SEM) and particle size analyser (PSA). The SEM image of the nanoparticles showed that most of them have irregular morphological shape. The nanoparticle size distribution is within the range of 490827 nm with the average surface charge of about -10.55 mV. The immobilized lipase specific activity in nanoparticles was 2,374 units/mg, which was lower than the free lipase that had a specific activity of 5,023 units/mg. This is the preliminary experiment to immobilize lipase by levan. Some optimizations still need to be carried out both in the nanomaterial production stage and in the lipase activity assay at the immobilized state.